Characterization of the CO2 System in a Coral Reef, a Seagrass Meadow, and a Mangrove Forest in the Central Red Sea. Issue 11 (11th November 2019) - Saderne, Vincent; Baldry, Kimberlee; Anton, Andrea; Agustí, Susana; Duarte, Carlos M.
Abstract: The Red Sea is characterized by its high seawater temperature and salinity, and the resilience of its coastal ecosystems to global warming is of growing interest. This high salinity and temperature might also render the Red Sea a favorable ecosystem for calcification and therefore resistant to ocean acidification. However, there is a lack of survey data on the CO2 system of Red Sea coastal ecosystems. A 1‐year survey of the CO2 system was performed in a seagrass lagoon, a mangrove forest, and a coral reef in the central Red Sea, including fortnight seawater sampling and high‐frequency pHT monitoring. In the coral reef, the CO2 system mean and variability over the measurement period are within the range of other world's reefs with pHT, dissolved inorganic carbon (DIC), total alkalinity (TA), p CO2, and Ωarag of 8.016±0.077, 2061±58 μmol/kg, 2415±34 μmol/kg, 461±39 μatm, and 3.9±0.4, respectively. Here, comparisons with an offshore site highlight dominance of calcification and photosynthesis in summer‐autumn, and dissolution and heterotrophy in winter‐spring. In the seagrass meadow, the pHT, DIC, TA, p CO2, and Ωarag were 8.00±0.09, 1986±68 μmol/kg, 2352±49 μmol/kg, 411±66 μatm, and 4.0±0.3, respectively. The seagrass meadow TA and DIC were consistently lower than offshore water. The mangrove forest showed the highest amplitudes of variation, with pHT, DIC, TA, p CO2, and Ωarag, were 7.95±0.26, 2069±132 μmol/kg, 2438±91 μmol/kg, 493±178 μatm, and 4.1±0.6, respectively. We highlight the need for more research on sources and sinks of DIC and TA in coastal ecosystems. Plain Language Summary: Global warming and ocean acidification are consequences of increased CO2 emissions to the atmosphere by humankind and are major threats to marine ecosystems. The Red Sea waters are naturally warm and saline. The resilience of its coral reefs, mangrove forests, and seagrass meadows is of growing interest for the scientific community in the context of global warming. The high temperature and salinity might render the Red Sea quite resistant to ocean acidification as well as an environment chemically very favorable for calcification, notably by corals. Calcification is a process dampened by the acidity (pH) of water, which depends on the chemistry of CO2 in seawater. Warm and saline water naturally tend to have a more basic pH and then be less corrosive to calcareous skeletons. However, the chemistry of the CO2 and acidity baselines and variability in the Red Sea are poorly documented. We conducted a year‐round survey of the CO2 chemistry of seawater in a seagrass meadow, mangrove forest, and coral reef ecosystem, involving discrete water sampling and high‐frequency measurements. Key Points: Dominance of heterotrophy and dissolution in winter‐spring and autotrophy and calcification in summer‐autumn in the coral reef Negative anomaly of TA and DIC in the seagrass meadow relative to offshore water The mangrove forest exhibited the widest variations but no systematic anomaly of TA and DIC relative to offshore water